Targeting Vascular endothelial growth factor A with soluble vascular endothelial growth factor receptor 1 ameliorates nerve injury-induced neuropathic pain. (15th April 2022) - Peng, Zhe; Yang, Fan; Huang, Siting; Tang, Yang; Wan, Li
Neuropathic pain is a distressing medical condition with few effective treatments. The role of Vascular endothelial growth factor A (VEGFA) in inflammation pain has been confirmed in many researches. However, the mechanism of VEGFA affects neuropathic pain remains unclear. In this study, we demonstrated that VEGFA plays an important role in spare nerve injury (SNI)-induced neuropathic pain, which is mediated by enhanced expression and colocalized of VEGFA, p-AKT and TRPV1 in SNI-induced neuropathic pain model. Soluble VEGFR1 (sFlt1) not only relieved mechanical hyperalgesia and the expression of inflammatory markers, but ameliorated the expression of VEGFA, VEGFR2, p-AKT, and TRPV1 in spinal cord. However, these effects of sFlt1 can be blocked by rpVEGFA and by 740 Y-P. Therefore, our study indication that targeting VEGFA with sFlt1 reduces neuropathic pain development via the AKT/TRPV1 pathway in SNI-induced nerve injury. This study elucidates a new therapeutic target for neuropathic pain.